Faktor Risiko Kejadian Gizi Kurang pada Anak Balita di Puskesmas Palla Kabupaten Sumba Barat Daya - Anita Bili; Lewi Jutomo; Daniela L. A. Boeky (Universitas Nusa Cendana, 2020)
This study aims to analyze the factors associated with the risk of malnutrition in children under five at Palla Primary Health Care, Southwest Sumba District. The type of research was analytical observation with a case-control design. The sample of case and control consisted of 46 people per group. Data analysis was performed by calculating Odds Ratio (OR). The results showed that infectious diseases (OR= 2,590), mothers’ knowledge related to nutrition (OR=2,615), energy (OR= 2,067) and protein (OR=2,254) consumption were risk factors for malnutrition among children under five. It can be concluded that infectious diseases, maternal knowledge of nutrition, energy and protein consumption have an important role as a risk factor for the incidence of malnutrition in children under five.